Resiliência: de que se trata?: o conceito e suas imprecisões - Juliana Mendanha Brandao (2009)
This research is a theoretical study on the concept of resiliency based upon referential texts of national and international literature on the theme. It was motivated by the identification of a wide variety of concepts of resiliency and by the lack of consensus among researchers concerning which phenomenon should be investigated: resistance to stress, represented by a subject that do not give up in the face of risk situations; or coping processes and recovery after traumas suffered because of adversity. First, historic and etymologic sources of resiliency are discussed, as well as its concept in materials resistance. Then, is shown a rewriting of the history of the studies of resiliency at international and national spheres, and the idea that resiliency concept came from physics is questioned. The main precursors studies on the subject are discussed, as well as the concept of invulnerability, prior nomenclature for the phenomenon. Next, is introduced the current understanding of resiliency and discussions about the concept to be understood as a trait or process, as innate or acquired, as permanent or circumstantial. The conceptualizations of resiliency are divided into two major groups: one that includes the conceptions associated to adaptation and one that covers settings in which it is understood as overcoming. It is also discussed ways to understand adaptation that are associated with the concept of resiliency: as proposed by Piaget; as an effective adjustment linked to the concept of competence; or in a sense of criticism to the society. It is also discussed the concepts in which survival already would imply resiliency and that this could be seen in an individual that still presents psychotic mental illness and anti social behavior. Finally, we classify resilience as a process rather than trait and propose our definition to the concept the process where a individual faces odds, suffers, overcomes the failings and his own trauma and gets mature\ stronger, learning from this process by choosing to consider resilience as a recovery phenomena and not the resistance to stress. This definition brings greater precision to the field of study. We also propose the concept of hardiness to study the phenomenon of resistance to stress, associated with trait of personality.